2019
DOI: 10.1016/j.bbr.2018.12.044
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amphetamine on working memory and locomotor activity in adult rats administered risperidone early in life

Abstract: Antipsychotic drugs are used to manage symptoms of pediatric psychiatric disorders despite the relative absence of research regarding the long-term effects of these drugs on brain development. Using rats as a model, research has demonstrated that administration of the antipsychotic drug, risperidone, during early postnatal development elevates locomotor activity and sensitivity to the locomotor effects of amphetamine during adulthood. Because risperidone targets neurotransmitter receptors and forebrain regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The psychostimulant properties of amphetamine depend on its modulation of both the noradrenergic and dopaminergic systems ( Fleckenstein et al, 2007 ). Amphetamine regulation of memory processes has been studied for many decades ( Martinez et al, 1983 ; Oscos et al, 1988 ; Bardgett et al, 2019 ). It has been shown that amphetamine-dependent enhancement of memory consolidation depends on the noradrenergic system stimulation properties ( Lee and Ma, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychostimulant properties of amphetamine depend on its modulation of both the noradrenergic and dopaminergic systems ( Fleckenstein et al, 2007 ). Amphetamine regulation of memory processes has been studied for many decades ( Martinez et al, 1983 ; Oscos et al, 1988 ; Bardgett et al, 2019 ). It has been shown that amphetamine-dependent enhancement of memory consolidation depends on the noradrenergic system stimulation properties ( Lee and Ma, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature data demonstrated that amphetamine induces profound effects on learning and memory processes. While it generally enhances memory consolidation, it has been shown that it increases memory retrieval errors and alters working memory performances ( Martinez et al, 1980a ; Ballard et al, 2014 ; Bardgett et al, 2019 ). Interestingly, it has been shown that amphetamine effects on memory consolidation are dependent on the amphetamine-induced activation of the noradrenergic system ( Lee and Ma, 1995 ; Colucci et al, 2019 ), a neurotransmitter system critically involved in the modulation of long-term memory consolidation ( Ferry et al, 1999 ; Roozendaal and McGaugh, 2011 ; McLumiere et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%